Postnatal expression of corticotropin releasing factor (CRF) in rat urinary bladder - LaBerge, Jennifer (2008)
Corticotropin releasing factor (CRF) is a neuropeptide expressed in micturition reflex circuitry and different roles in these reflexes have been suggested. These studies examined the expression of CRF/CRF receptors in the urinary bladder during postnatal development in the rat. Urinary bladder was harvested from rats (postnatal (P) day 0-adult) euthanized by isoflurane (4%) and thoracotomy. CRF protein expression significantly (p ≤ 0.01) decreased in the urothelium with increasing postnatal age. In contrast, CRF-immunoreactivity (IR) was increased in nerve fibers in the suburothelial plexus during the second-third postnatal week. Total CRF protein from urinary bladder significantly increased during the second-third postnatal weeks as determined with ELISAs. CRF receptor 2 (CRFR(2)) transcript was expressed in urinary bladder of all postnatal ages examined whereas no CRFR(1) transcript was expressed at any postnatal age examined. We also demonstrated changes in urinary bladder mRNA expression for the neuropeptides, galanin, substance P, vasoactive intestinal polypeptide and pituitary adenylate cyclase activating polypeptide during postnatal development. These studies demonstrate changes in the CRF expression in urinary bladder, specifically in the urothelium and nerve fibers of the suburothelial plexus during postnatal development. Changes in CRF expression and neuropeptide expression in general in the urinary bladder may contribute to the emergence of mature voiding reflexes.